Some biological properties of new sweet cherry cultivars in Bulgaria and their susceptibility to Blumeriella jaapii - Borovinova, M.; Christov, N.; Nyéki, J. (International Journal of Horticultural Science, 2007)
Investigations were made on 12 sweet cherry cultivars (‘13-S-22-8’, 'Sunburst', `Kozerska'., 'NY 13791', 'Royalton', 'NY 13688', 'Hartland', `Sumerset', 'Pollax', 'Patriotka Krima', 'Castor', and `Lapins') in an experimental orchard of cherry cultivar collection in the Institute of Agriculture at Kyustendil, Bulgaria during the period of 1997-2003. The trees were planted in 1996. All cultivars were grafted on Prunus mahaleb. Four biological properties of the cultivars were assessed such as blooming time, resistance to late spring frost, fruit ripening and fruit mass. Among cultivars, a good resistance to late spring frost was observed on cultivar 'Sunburst'. The fruit mass varied between 4.2 g (cv. 'Patriotka Krima') and 8.5 g (cv. `Sunburst'). The susceptibility of the cherry cultivars to cherry leaf spot caused by Blumeriella jaapii was assessed in mid-September in each year. The estimation of the rate of attack was made according to the grade of Townsend and Neuberger. All cultivars showed symptoms of cherry leaf spot but the degree of susceptibility was different. Cultivar `Patriotka Krima' was the least susceptible, while cultivar `Somerset' was the most susceptible to Blumeriella jaapii.